2020
DOI: 10.1590/1413-81232020258.21522018
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem espacial da hanseníase no estado da Bahia, Brasil, (2001-2015) e determinantes sociais da saúde

Abstract: Resumo O trabalho analisa a distribuição espacial da hanseníase na Bahia e os determinantes sociais relacionados. Estudo ecológico com dados de hanseníase do período 2001-2015. Três indicadores epidemiológicos foram selecionados: coeficiente de detecção na população geral e em menores de 15 anos e a taxa de casos novos com grau II de incapacidade. Os indicadores foram suavizados pelo Modelo Bayesiano Empírico Local e aplicou-se estatística de Moran Global e Local. As variáveis independentes foram selecionadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
6
0
3
Order By: Relevance
“…The presence of agglomerates in Manaus and the metropolitan region is linked to a social scenario in which social inequality, competitiveness and fragile relations between municipalities prevail, resulting in an insufficient network of health services and a quantitative deficiency of human resources [21, 30]. The direct relationship of social vulnerability, expressed by the SVI, which verifies population conditions in addition to economic aspects, including housing and education conditions, corroborates to explain the existence of spatial clusters in these regions, since factors that express poverty increase the risk of transmission by infectious diseases [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of agglomerates in Manaus and the metropolitan region is linked to a social scenario in which social inequality, competitiveness and fragile relations between municipalities prevail, resulting in an insufficient network of health services and a quantitative deficiency of human resources [21, 30]. The direct relationship of social vulnerability, expressed by the SVI, which verifies population conditions in addition to economic aspects, including housing and education conditions, corroborates to explain the existence of spatial clusters in these regions, since factors that express poverty increase the risk of transmission by infectious diseases [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the influence of income per capita on the outcomes studied is related to the presence of a better network of health services, expanding the population's access to carrying out diagnostic tests in the municipalities with the highest per capita income. Corroborating this finding, GWR analysis revealed that coverage of primary health care is directly related to the incidence of COVID-19, since expanding access increases the number of diagnosed cases and reduces underreporting, contributing to increasing the coefficients incidence and mortality [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNI involved four variables: 1) Economic and Social Performance-Economy and Finance Index (IPESE-EF), (2) average monthly value of per capita income (RENDAPERCAPIT), (3) proportion of extremely poor (%EXTRPOBRES), and (4) number of households with density larger than three persons per room (DOM3PPDOR). These variables were selected from previous studies in which these indicators were associated with the dynamics of leprosy transmission in Bahia state 4 , 7 . After the calculation, the municipalities were classified into quartiles: low SNI (0.142 to 0.259), medium SNI (0.260 to 0.369), high SNI (0.370 to 0.479), and very high SNI (0.480 to 0.699).…”
mentioning
confidence: 99%
“…Several investigations have shown that the risk of leprosy is high among people living in poor living conditions 4 , 5 , 7 , 9 . Income inequality, social vulnerability, poverty, poor housing conditions, poor diet, and low educational level are considered social determinants related to disease transmission 4 , 5 , 7 , 9 . However, poor conditions may inhibit the early diagnosis, thus increasing the hidden prevalence, which justifies the low coefficients observed in the strata of higher SNI.…”
mentioning
confidence: 99%